Targeted transcriptomic analysis of well-differentiated and dedifferentiated liposarcoma reveals multiple dysregulated pathways including glucose metabolism, TGF-β, and HIF-1 signaling - Patton, Ashley; Horn, Natalie; Upadhaya, Puja; Sarchet, Patricia; Pollock, Raphael E.; Oghumu, Steve; Iwenofu, Obiajulu Hans (Frontiers in Oncology, 2024)
Liposarcoma is the most prevalent sarcoma in adults representing 20% of all sarcomas with well-differentiated/dedifferentiated among the most common subtypes represented. Despite multimodality treatment approaches, there has not been any appreciable change in survival benefit in the past 10 years. The future of targeted therapy for WD/DDLPS is promising with the intention to spare multi-visceral removal due to radical surgical resection. Therefore, there is a need to expand upon the molecular landscape of WDLPS and DDLPS which can help identify potential therapeutic targets for the treatment of this disease. Targeted transcriptome analysis using the NanoString tumor signaling 360 panel revealed a dysregulation in glucose metabolism and HIF1 signaling pathways in both WDLPS and DDLPS when compared to normal fat controls. WDLPS, however, demonstrated upregulation of HIF-1A and TGF-β when compared to DDLPS by targeted transcriptome analysis and orthogonal validation by RT-qPCR suggesting activation of EMT pathway in WDLPS when compared to DDLPS. Our findings implicate a putative role for dysregulation in glucose metabolism, TGF-β and HIF1 signaling in the pathogenesis of both WD/DDLPS suggesting a possible proinflammatory tumor environment within WDLPS and subsequent activation of the TGF-β signaling pathway.